Value-at-Risk: the Relation with Profit and Other Risk Indicators - Li, Shujia (2007)
Value-at-Risk is perhaps the most distinguish terminology in risk management area. Due to its high popularity, some people treat it as the only risk indicator for a company. When evaluate the "risk and return" relation for decision making, they sometimes solely consider VaR as the risk indicator. This dissertation has tested VaR's predicable power on banks' return parameter- profit value and found no relationship between VaR and profit. Three other risk indicators, namely derivative usage, market beta and leverage ratio have been tested against profit. It is found that Derivative and Beta both positively related to Profit while Leverage has no relationship with Profit.